Penentuan Prioritas Penanganan Genangan di Kecamatan Warudoyong, Kota Sukabumi - Audi Anugrah Somali; Eka Wardhani (Jurnal Serambi Engineering, 2025)
Warodoyong District is the district with the most puddles in Sukabumi City, with 9 puddles. The 9 puddles need to be prioritised. The purpose of this study is to calculate the priority value for handling puddles that occur in Warodoyong District. It is hoped that this study can be used by the Sukabumi City Regional Government and related agencies in handling puddles that occur. The determination of puddle management priorities is based on the Minister of Public Works Regulation No. 12 of 2014 on the Implementation of Urban Drainage Systems. Based on the results of the weighting carried out, puddle G1 has the highest value of 336, so it becomes the main priority in handling puddles that occur. Efforts to deal with puddles immediately are necessary because puddles occur in areas used by the community in their daily activities.